Citizen Science: The First Peninsular Malaysia Butterfly Count - Wilson, J.J.; Jisming-See, S.W.; Brandon-Mong, G.J.; Lim, A.H.; Lim, V.C.; Lee, P.S.; Sing, K.W. (Pensoft Publishers, 2015)
Background Over the past 50 years, Southeast Asia has suffered the greatest losses of biodiversity of any tropical region in the world. Malaysia is a biodiversity hotspot in the heart of Southeast Asia with roughly the same number of mammal species, three times the number of butterfly species, but only 4% of the land area of Australia. Consequently, in Malaysia, there is an urgent need for biodiversity monitoring and also public engagement with wildlife to raise awareness of biodiversity loss. Citizen science is "on the rise" globally and can make valuable contributions to long-term biodiversity monitoring, but perhaps more importantly, involving the general public in science projects can raise public awareness and promote engagement. Butterflies are often the focus of citizen science projects due to their charisma and familiarity and are particularly valuable "ambassadors" of biodiversity conservation for public outreach. New information Here we present the data from our citizen science project, the first "Peninsular Malaysia Butterfly Count". Participants were asked to go outdoors on June 6, 2015, and (nonlethally) sample butterfly legs for species identification through DNA barcoding. Fifty-seven citizens responded to our adverts and registered to take part in the butterfly count with many registering on behalf of groups. Collectively the participants sampled 220 butterfly legs from 26 mostly urban and suburban sampling localities. These included our university campus, a highschool, several public parks and private residences. On the basis of 192 usable DNA barcodes, 43 species were sampled by the participants. The most sampled species was Appias olferna, followed by Junonia orithya and Zizina otis. Twenty-two species were only sampled once, five were only sampled twice, and four were only sampled three times. Three DNA barcodes could not be assigned species names. The sampled butterflies revealed that widely distributed, cosmopolitan species, often those recently arrived to the peninsula or with documented "invasive" potential, dominated the habitat types sampled by the participants. Data from this first Butterfly Count helps establish a baseline from which we can monitor the patterns and changes in butterfly communities in Peninsular Malaysia.